2013
DOI: 10.1177/1538192713481385
|View full text |Cite
|
Sign up to set email alerts
|

Differences Among Latino Students in Precollege Multicultural Exposure and the Transition Into an Elite Institution

Abstract: This study examined the within-group differences in adjustment to college among Latino college students. Surveys measured participants for degree of precollege multicultural exposure, current concerns, minority student stress, social resources, and sociocultural orientation. The findings suggested that the transition into a predominately White, highly selective institution was different for Latino students based upon multicultural exposure in their high school context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Hurtado and Ponjuan (2005) found that Latinx students who were more critical of the racial dynamics at their institution were more likely to be involved in co-curricular activities. Latinx students experiencing a negative campus climate often build communities that represent their cultural backgrounds and home communities; these counterspaces (which include academic and social spaces where students from underrepresented backgrounds have their experiences validated) provide a place to foster skills that assist them in navigating multiple spaces including home, community, and campus (Lopez, 2013; Yosso et al, 2009). Oftentimes, institutions expect students to assimilate or figure out how to navigate this new environment without providing the necessary support to assist students in bridging their home culture and the campus culture (Lopez, 2013), making the transition to college more difficult.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hurtado and Ponjuan (2005) found that Latinx students who were more critical of the racial dynamics at their institution were more likely to be involved in co-curricular activities. Latinx students experiencing a negative campus climate often build communities that represent their cultural backgrounds and home communities; these counterspaces (which include academic and social spaces where students from underrepresented backgrounds have their experiences validated) provide a place to foster skills that assist them in navigating multiple spaces including home, community, and campus (Lopez, 2013; Yosso et al, 2009). Oftentimes, institutions expect students to assimilate or figure out how to navigate this new environment without providing the necessary support to assist students in bridging their home culture and the campus culture (Lopez, 2013), making the transition to college more difficult.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Latinx students experiencing a negative campus climate often build communities that represent their cultural backgrounds and home communities; these counterspaces (which include academic and social spaces where students from underrepresented backgrounds have their experiences validated) provide a place to foster skills that assist them in navigating multiple spaces including home, community, and campus (Lopez, 2013; Yosso et al, 2009). Oftentimes, institutions expect students to assimilate or figure out how to navigate this new environment without providing the necessary support to assist students in bridging their home culture and the campus culture (Lopez, 2013), making the transition to college more difficult. Pérez and Taylor (2016) asserted the importance of institutions assisting Latinx students in translating their accumulated capital (prior knowledge and skills) to the college setting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…And the burden of bridging or integrating Latino/a students’ home cultures and the cultures of their campuses is often placed on the shoulders of the students themselves. Indeed, institutions often leave it up to Latino/a students to assimilate into the dominant cultures of PWIs (Hurtado & Ponjuan, ; Lopez, ). The challenges that Latino/a students face at PWIs, coupled with the continued assumption that responsibility to adjust lies primarily with these students, constitute a significant problem that warrants the attention of postsecondary educators.…”
Section: Campus Racial Climate and Campus Racial Culture At Predominamentioning
confidence: 99%
“…For example, a qualitative study by Rivas-Drake (2008) revealed three major patterns of behavior and thought that demonstrated the various ways a Latino identity is experienced and individually negotiated to be either at odds with or a primary source of motivation and perceived opportunity. Other studies have demonstrated how high school diversity plays an important role in determining successful transition into selective predominantly White institutions (Lopez, 2013) and how minorities are more likely to persist at selective institutions (Melguizo, 2008). Yet these studies do not address the conditions that promote measurable gains in academic or personal development at these institutions.…”
Section: Background and Literaturementioning
confidence: 99%